2007
DOI: 10.1097/wnn.0b013e3180653c35
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Syndrome as a Dimension: Factor Analyses of PANSS in Major Depressive Disorder and Organic Brain Disease Compared With Negative Syndrome Structures Found in the Schizophrenia Literature

Abstract: The negative syndrome may be a nosologic entity, which remains fairly consistent across psychotic and nonpsychotic diagnostic categories. Confirmatory studies are merited to determine the degree and strength of the similarity in structure of the negative syndrome in psychotic, affective, and cognitive illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
2
12
2
1
Order By: Relevance
“…However, given that 39% of participants had a primary diagnosis of schizophrenia, while 34% had a diagnosis of bipolar disorder and 27% had a diagnosis of major depressive disorder, the fact that the HRQoL preference weights were developed for schizophrenic health states identified via the PANSS is a limitation, as is the fact that, to the best of our knowledge, the mapping function has only been applied to and tested on individuals with a primary diagnosis of schizophrenia (Heeg et al, 2008; Järbrink et al, 2009; Lenert et al, 2005; Rabinowitz et al, 2013). Although, as discussed above, studies have shown similarities between schizophrenia and bipolar and major depressive disorders with regard to the psychotic symptom domains identified by the PANSS (Daneluzzo et al, 2002; Eisenberg et al, 2009; Lindenmayer et al, 2007, 2004; Milak et al, 2007; Purnine et al, 2000). Moreover, we only observed significant group differences on PANSS ratings related to mood lability, rather than psychotic symptoms, in a sample that was primarily mood disordered.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, given that 39% of participants had a primary diagnosis of schizophrenia, while 34% had a diagnosis of bipolar disorder and 27% had a diagnosis of major depressive disorder, the fact that the HRQoL preference weights were developed for schizophrenic health states identified via the PANSS is a limitation, as is the fact that, to the best of our knowledge, the mapping function has only been applied to and tested on individuals with a primary diagnosis of schizophrenia (Heeg et al, 2008; Järbrink et al, 2009; Lenert et al, 2005; Rabinowitz et al, 2013). Although, as discussed above, studies have shown similarities between schizophrenia and bipolar and major depressive disorders with regard to the psychotic symptom domains identified by the PANSS (Daneluzzo et al, 2002; Eisenberg et al, 2009; Lindenmayer et al, 2007, 2004; Milak et al, 2007; Purnine et al, 2000). Moreover, we only observed significant group differences on PANSS ratings related to mood lability, rather than psychotic symptoms, in a sample that was primarily mood disordered.…”
Section: Discussionmentioning
confidence: 96%
“…The PANSS was originally developed to measure symptom severity among individuals with schizophrenia, but it is also commonly used as a psychotic symptom assessment tool for individuals with mood disorders given that it assesses symptoms associated with such disorders, such as mood lability, depressed mood and hostility. Studies have shown the PANSS to identify similar psychotic symptom domains between patients with schizophrenia and bipolar disorder (Daneluzzo et al, 2002; Lindenmayer et al, 2007, 2004), and between schizophrenia and major depressive disorder (Eisenberg et al, 2009; Milak et al, 2007; Purnine et al, 2000) – the three serious mental disorders with which participants had been diagnosed. However, before the PANSS scores can be used to weight life years, they must be linked to a measure of utility and converted to the aforementioned 0-1 health-utility index.…”
Section: Methodsmentioning
confidence: 99%
“…The PANSS is widely used in patients with neuropsychiatric symptoms, and it has been found to have good sensitivity and specificity for psychosis and schizophrenia 2527,29…”
Section: Methodsmentioning
confidence: 99%
“…A commonly used and validated clinical scale was used to find psychosis and schizophrenia symptoms (the Positive and Negative Symptom Scale [PANSS]), which quantifies the broad spectrum of psychotic symptoms including positive and negative psychotic symptoms and formal thought disorders 23,24. As the PANSS is originally developed to prospectively evaluate psychotic symptomatology over time, it also includes a general subscale, wherein symptoms such as tension and anxiety are included 2527. The aim of the present study was to define psychotic symptoms in patients with probable and definite bvFTD in comparison with patients with a psychiatric disorder, all exhibiting a late-onset frontal lobe (LOF) syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…We chose a measure of negative symptoms as this concept encompasses areas that are highly relevant for MT: the ability (or its absence) to express oneself emotionally (affective flattening), the ability to form and sustain satisfactory relationships (anhedonia/asociality) and general motivation (avolition/apathy). Although negative symptoms are usually associated with schizophrenia, there is evidence that they are relevant for other disorders as well, notably for affective disorders [33,34,35,36,37]. Negative symptoms in themselves are strongly predictive of a need for care, irrespective of the primary diagnosis or whether the negative symptoms are considered primary or secondary [38].…”
Section: Methodsmentioning
confidence: 99%